Comparative analysis of Identification and Classification of Face Emotions Using Different Machine Learning and Deep Learning Algorithms - Dasharath K. Bhadangkar, Jagadeesh D. Pujari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Sentiments are significant and profound features of individual conduct. Examining facial looks and acknowledging their expressive condition is stimulating job by extensive reaching functions. Human Face expression Recognition is one of very influential and stimulating chores in public interaction. Usually, face expressions are usual and straight ways for human beings for communicate their emotions and intentions. Face expressions are the key characteristics of non-verbal communication. Here, we introduce available dataset i.e., CK+, JAFFE and FED dataset that are widely used in this work. This paper focuses upon facial expression recognition technique founded on machine learning algorithms pair and also deep learning algorithms that will assist in precise recognition and organization of human emotion.